Landmarking for Improved Digital Product Creation - Emma Scott; Katherine Schildmeyer; Gerald Ruderman; Susan Ashdown; Carolyn McDonald; Simeon Gill (Communications in Development and Assembling of Textile Products)
Sampling is a critical step in the concept-to-style workflow for digitally created products. Virtual environments allow sampling without the costs associated with physical prototyping However, current practice often still requires physical prototyping. Here we consider how landmarking contributes to the need for iterative sampling, thereby inhibiting a fully digital product creation DPC process. In the process, the opportunity for error within traditional anthropometric study is highlighted and a path toward global standardized landmarking and measuring (L&M) is presented. Landmarks denote anatomical reference points common to all humans. They are critical to every stage of DPC: measuring, product development, virtual sampling, rigging, size selection, and try-on. Cross-platform use of humanoids (models of humans) and body-worn products will introduce errors if landmarking protocols do not align across three-dimensional body processing (3DBP) technologies. Here we discuss how to avoid these discrepancies by combining Clone Block™ theory with current ISO standards. Further study should validate the findings here for the implementation of global standardized L&M to facilitate 3D technology interoperability, fully DPC, and greater adoption of 3D technologies for improved fit of body-worn products.